Study of balancing methods for parallel cable transmission lines - Jiayin Bian; Jue Zhang; Shiqi Kong; Wanlin Quan; Weiming He (AIP Advances)
Cables are of vital importance for the transmission and distribution of electricity within the power grid. However, as the demand for electricity continues to grow, the transmission capacity of a single high-voltage cable is no longer sufficient to meet the required standards. It is therefore imperative to increase the transmission capacity of cables. The deployment of parallel cable transmission represents the most effective strategy for enhancing transmission capacity. However, due to the complex electromagnetic coupling relationship between cables, there is a possibility of current imbalance between cable lines in the same phase, which will have an adverse effect on the normal operation of power equipment and pose a significant threat to the security of the power system. In light of the aforementioned considerations, this paper primarily investigates the mitigation of parallel cable line imbalance. Initially, it examines the parallel cable line current imbalance factors through a theoretical lens, encompassing cable impedance and electromagnetic coupling arrangement. Subsequently, it assesses the efficacy of two proposed methods for reducing the imbalance degree of the parallel cable, namely, the adjustable reactor in series and the addition of a magnetic ring device. Furthermore, finite element simulation software is employed to simulate the two methods and verify their efficacy. Ultimately, a parallel cable plus magnetic ring test is conducted to verify the effectiveness of the magnetic ring.